Tailored anthocyanin delivery through modulating -COOH groups in pH-responsive peptide gels - Wenjun Li; Qianqian Bie; Jianling Li; Wenjie Yang; Pengliang Cao; Wenyu Yang; Xianggui Chen; Pengfei Chen (Food Chemistry: X)
With the continuous advancement of precision nutrition, researchers have increasingly recognized the need for tailored, stable delivery of food bioactive compounds, such as anthocyanins, in response to the varying conditions of the gastrointestinal (GI) environment. In this proof-of-concept study, we hypothesize that by modulating the number of pH-responsive -COOH groups in peptide gels, we can precisely control their pH responsiveness, rheological properties, and other physicochemical characteristics, enabling efficient anthocyanin delivery under diverse GI conditions. Our experiments demonstrate that increasing the number of -COOH groups and amino acids in the peptide sequence enhances the pH responsiveness, rheological properties, and stability of anthocyanin molecules within the gels, without compromising their biocompatibility or altering their release rate. These results validate our hypothesis and offer a customizable solution for meeting the diverse delivery needs of gastrointestinal environments. It may enrich the tools available for precise nutritional delivery, enhancing their bioavailability and therapeutic potential.